2018
DOI: 10.1016/j.ajog.2017.11.583
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone therapy in endometrial cancer

Abstract: We read with interest the paper “All-cause mortality in young women with endometrial cancer receiving progesterone therapy” by Maria P. Ruiz et al (1). The authors reported that the use of primary progesterone therapy increased significantly from 2004 to 2014 and that utilization was less frequent in older women, white women, and women with unfavorable grading and substaging. Moreover, the authors note, “its use was associated with decreased survival, particularly in women with stage IB tumors“.\ud The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Large doses of progesterone can directly act on cancer cells, inhibit the synthesis of cellular DNA and RNA, and reduce cell division, thus inhibiting cell proliferation. 6,7) As a nonsteroidal anti-estrogenic drug, tamoxifen (TAM) increases the expression of progesterone receptors, and its application in combination with progesterone can improve the therapeutic effect of the latter. 8,9) Recent studies have shown that TAM can increase the stemness and metastasis of estrogen receptor (ER)α36-positive breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Large doses of progesterone can directly act on cancer cells, inhibit the synthesis of cellular DNA and RNA, and reduce cell division, thus inhibiting cell proliferation. 6,7) As a nonsteroidal anti-estrogenic drug, tamoxifen (TAM) increases the expression of progesterone receptors, and its application in combination with progesterone can improve the therapeutic effect of the latter. 8,9) Recent studies have shown that TAM can increase the stemness and metastasis of estrogen receptor (ER)α36-positive breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%